Axiology and dynamics of contemporary research groups: a systematic review and hermeneutic meta-analysis of knowledge, values, and social elements - Ayala, Edgar O.; Altamirano-Bustamante, Myriam M.; de Hoyos-Bermea, Adalberto (Frontiers in Research Metrics and Analytics, 2025)
IntroductionThis research explores the practices of current research groups, where multidisciplinary groups stand out for their relevance in developing science. The objective is to comprehensively explore the practices and values of research groups through a three phase study.MethodsIn the first phase a systematic review was performed, in the second phase, a hermeneutic analysis focused on values, knowledge and the social elements to describe and delve into the development of scientific practices. The third phase, a discussion of these practices and interactions was proposed.ResultsThe most relevant findings are the specific attitudes valued in social interactions, such as the relationship between cooperation and solidarity, economic values like the link between benefit and profitability, and research values like the connection between inclusion and coherence.DiscussionThese relationships help define the value networks that shape interactions, practices and relationships within scientific groups. This describes the dynamic of contemporary science to answer today's challenges.